SITE PROCESSING ASSESSMENT TYPE A BUS TERMINAL IN SURAKARTA BASED ON ECO-TECH ARCHITECTURE THEORY - Fika Aura Ratitya (Universitas Pendidikan Indonesia, 2022)
Abstract - Problems that are often seen in bus terminals are identical to air pollution, noise pollution and excessive use of energy in their operations, so that the bus terminal has a negative impact on the surrounding environment. Solving these problems can be done by site processing that applies Eco-Tech architectural theory. Eco-Tech architecture encourages environmentally-based designs combined with smart building design technology, is energy efficient, environmentally friendly and provides a sense of comfort for users. The theory is closely related to the principle of Green Building, where building design now must refer to the concept of green buildings. Assessment can be through the Greenship reference standard set by the Green Building Council Indonesia (GBCI). One of the principles used in this assessment is appropriate land use management at the type A bus terminal site in Surakarta. This principle aims to assess and determine the condition of the site and its surroundings, the efficiency of land management, and rainwater treatment in the site in the future. This research method uses a qualitative method and provides an index value based on secondary data through the problem identification stage, inputting theory and literacy which is then followed by data analysis, and produces a conclusion, namely the application of this principle has not been fully applied to the design of the bus terminal in Surakarta.Keywords – Bus station, Surakarta City, Appropriate site, Eco-Tech